IMPLEMENTASI ASAS KEBERMANFAATAN DALAM UNDANG-UNDANG NOMOR 19 TAHUN 2013 TENTANG PERLINDUNGAN DAN PEMBERDAYAAN PETANI DI KECAMATAN KUPANG TIMUR - Oematan, Naldi Edison (Penerbit Universitas Atma Jaya Yogyakarta, 2024)
The formulation of Law No. 19 of 2013 on the Protection and Empowerment of Farmers (P3 Law) is equipped with the principle of usefulness, the presence and strength of the norms that are carried are able to support every pulse of the lives of farmers. In accordance with the intention of the formulators of this law to empower and protect farmers, the principles also complement the guidelines in its implementation and the goals envisioned together. This paper uses empirical legal research method which looks at the applicable rules and how they are implemented in society. For the formulation of the problem that is trying to be examined is how the application of the Principle of Benefit in Law Number 13 of 2019 concerning Protection and Empowerment of Farmers and what is the responsibility of the Government in the protection of Farmers from the perspective of Welfare Theory. For the application of the principle of usefulness in the P3 Law, there are still obstacles about how the protection and empowerment of farmers is not optimal and reaches the problems of farmers in farming activities. For the government's responsibility in the protection of farmers is still not optimal where vulnerability in crop failure and farming risks, the vulnerability of farmers in Kupang Regency has not been maximally collected.